MANAJEMEN SISTEM PENILAIAN YANG EFEKTIF DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM - Rofii'atul Fitriyyah (Pascasarjana Universitas PTIQ Jakarta, 2025)
Improving the quality of Islamic education in the midst of globalization and digitalization has become a necessity that demands an effective assessment system. This study aims to comprehensively analyze the concept of assessment system management, its implementation models, the role of technology, and strategic challenges and solutions in the context of improving the quality of Islamic education based on literature studies from indexed journals. The method used is a literature study by analyzing relevant articles from the database. The main findings show that effective assessment system management involves planning, designing, implementing, monitoring, and continuous evaluation. There is a close relationship between effective assessment and improving the quality of Islamic education holistically, which includes not only cognitive aspects, but also affective and spiritual aspects. Various innovative assessment models such as competency-based, authentic, formative assessment, and those integrated with Total Quality Management (TQM) are identified as relevant approaches. Technology plays a crucial role in optimizing the assessment system, although its implementation is faced with structural and cultural challenges. This study concludes that adaptive, integrated, and data-based assessment system management is a fundamental prerequisite for realizing quality Islamic education that is relevant to the demands of the times. The implications of these findings are intended for policy makers, education practitioners, and researchers to develop and implement better assessment systems to support the advancement of Islamic education. Understanding that the quality of Islamic education goes beyond academic achievement, requires an assessment system that is able to measure dimensions of student development as a whole, including character and spirituality.